2002
DOI: 10.4049/jimmunol.168.9.4559
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Involved in IL-8-Dependent Activation of Adhesion Through Mac-1

Abstract: In human neutrophils, IL-8 induces chemotaxis, the respiratory burst, and granule release, and enhances cellular adhesion, a β2 integrin-dependent event. IL-8 stimulates neutrophil adhesion to purified fibrinogen in a Mac-1-dependent manner. Mitogen-activated protein kinase (MAPK) activation was detected in human neutrophil lysates after treatment with IL-8 and PMA, but not the activating mAb CBR LFA 1/2. IL-8-stimulated neutrophil adhesion to fibrinogen was blocked 50% by the MAPK/extracellular signal-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 55 publications
1
56
1
4
Order By: Relevance
“…IL-8 induces the neutrophil respiratory burst and granule release, and enhances cellular adhesion, a β2 integrin-dependent event. IL-8-induced β2 integrin activation may be mediated through Mitogen-activated protein kinase (MAPK) and Protein Kinase C (PKC) signaling [104]. It appears that neutrophils may need to sample immobilized IL-8 molecules presented by the vessel wall before forming a sufficient number of high avidity β2 integrin bonds for firm adhesion [105].…”
Section: Chemokines In Healing Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-8 induces the neutrophil respiratory burst and granule release, and enhances cellular adhesion, a β2 integrin-dependent event. IL-8-induced β2 integrin activation may be mediated through Mitogen-activated protein kinase (MAPK) and Protein Kinase C (PKC) signaling [104]. It appears that neutrophils may need to sample immobilized IL-8 molecules presented by the vessel wall before forming a sufficient number of high avidity β2 integrin bonds for firm adhesion [105].…”
Section: Chemokines In Healing Infarctionmentioning
confidence: 99%
“…It appears that neutrophils may need to sample immobilized IL-8 molecules presented by the vessel wall before forming a sufficient number of high avidity β2 integrin bonds for firm adhesion [105]. In addition, IL-8 may also have effects beyond its neutrophil chemotactic properties [104]. IL-8 neutralization significantly reduces the degree of necrosis in a rabbit model of myocardial ischemia-reperfusion injury without affecting neutrophil infiltration [106].…”
Section: Chemokines In Healing Infarctionmentioning
confidence: 99%
“…This could be potentially important, considering the evidence suggesting that the signaling pathways governing locomotion vary depending on the stimulus. Previous studies (53)(54)(55)(56)(57) showed that FMLP and C5a activate chemotaxis through p38 MAPK , while IL-8 uses the PI3K pathway. IL-8 activates ERK2 (p42 MAPK ), but this is apparently unrelated to its effect on chemotaxis.…”
Section: Figure 10mentioning
confidence: 99%
“…PC-3 cells were grown and treated with or without G31P (up to 100 ng/ml) in a serum-free medium for 24 h. Then, the cells were seeded at 3 × 10 5 cells/well in the pre-coated plates, incubated for 1 h at 37°C, and gently washed three times with PBS. The remaining adhered cells were enumerated using the same cell counting reagent as above, and the absorbance rate at 450 nm was determined with a 96-well plate reader (Takami et al 2002).…”
Section: Cell Adhesion Assaymentioning
confidence: 99%